Implementation of CBNA (Computer Based National Assessement) on Students Mental Readiness - Pratama, M. Arifky; Na'imah, Zannatun; Permatasari, Iin; Pradana, Oryza Putra; Pitriani, Yetri (Universitas Riau Kepulauan, 2023)
ABSTRACTThe government through the Minister of Education and Culture circular letter Number 1 of 2021 decided that the National Examination would be abolished and prohibited by the National Assessment. Assessment is an activity to reveal the quality of the process and learning outcomes. In its implementation it is carried out computer-based so that it is called the Computer-Based National Assessment. ANBK is an assessment or assessment that is carried out at every stage of school starting from SD, SMP/MTS, SMA/SMK equivalent. The purpose of this study was to find out how the implementation of ANBK in elementary schools and students' mental readiness in dealing with ANBK. This research method uses a descriptive qualitative approach with participants consisting of the Principal, Class V teacher and 2 students who were randomly selected from MIN 2 South Bengkulu. Data collection instruments in this study used observation, interview guides and field notes. The results of this study indicate that the implementation of ANBK at MIN 2 South Bengkulu is due to facilities constraints in the form of computers from each MIN 2 South Bengkulu which are less qualified. Then the mental readiness of students can know that students who are caught taking ANBK experience exam anxiety caused by an ingrained mindset that the National Assessment is a substitute for the National Examination so they are of the view that they have to do the Assessment seriously in order to get good and satisfying grades.